Atomic Force Microscopy Study of Cross-Sections of Perovskite Layers - Migunov, D.; Eidelman, K.; Kozmin, A.; Saranin, D.; Ermanova, I.; Gudkov, D.; Alekseev, A. (EURASIAN CHEMICO-TECHNOLOGICAL JOURNAL, 2019)
Improvement of methods for imaging of the volume structure of photoactive layers is one of the important directions towards development of highly efficient solar cells. In particular, volume structure of photoactive layer has critical influence on perovskite solar cell performance and life time. In this study, a perovskite photoactive layer cross-section was prepared by using Focused Ion Beam (FIB) and imaged by Atomic Force Microscopy (AFM) methods. The proposed approach allows using advances of AFM for imaging structure of perovskites in volume. Two different types of perovskite layers was investigated: FAPbBr(3) and MAPbBr(3). The heterogeneous structure inside film, which consist of large crystals penetrating the film as well as small particles with sizes of several tens nanometers, is typical for FAPbBr(3). The ordered nanocrystalline structure with nanocrystals oriented at 45 degree to film surface is observed in MAPbBr(3). An optimized sample preparation route, which includes FIB surface polishing by low energy Ga ions at the angles around 10 degree to surface plane, is described and optimal parameters of surface treatment are discussed. Use of AFM phase contrast method provides high contrast imaging of perovskite structure due to strong dependence of phase shift of oscillating probe on materials properties. The described method of imaging can be used for controllable tuning of perovskite structure by changes of the sample preparation routes....
Keywords: perovskite; nanostructure; atomic force microscopy; focused ion beam; cross-section